2012
DOI: 10.1007/s00405-012-2106-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of round window accessibility to cochlear implant insertion

Abstract: Emphasis on hearing preservation has led to recognition of the round window membrane (RWM) as a portal for the cochlear implant electrode array. The St Thomas' Hospital (STH) classification was devised to evaluate the accessibility of RWM electrode insertion. The objectives of this study were: (1) to prospectively evaluate the STH classification in selecting the appropriate cochlear insertion route in "RWM-intentioned" cases, and (2) to ascertain if RWM accessibility differs from adults to children. This was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
70
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(78 citation statements)
references
References 14 publications
1
70
1
Order By: Relevance
“…Total exposure of the RW will allow RW insertion of the cochlear implant electrodes. Leong et al (11) reported that the RW was visible in more than 50% to 89% of adult and 78% of paediatric cases after an optimal posterior tympanotomy. In cases in which the RW niche cannot be totally exposed, one must keep in mind that further dissection of the anatomic boundaries may cause complications such as facial paralysis and taste disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Total exposure of the RW will allow RW insertion of the cochlear implant electrodes. Leong et al (11) reported that the RW was visible in more than 50% to 89% of adult and 78% of paediatric cases after an optimal posterior tympanotomy. In cases in which the RW niche cannot be totally exposed, one must keep in mind that further dissection of the anatomic boundaries may cause complications such as facial paralysis and taste disorders.…”
Section: Discussionmentioning
confidence: 99%
“…RW insertion using the posterior tympanotyomy approach can be more challenging in some cases with limited visibility of the RW. This restricted exposition occurs in 11-22% of children, and conventional bony cochleostomy may then be required [4] . Facial nerve injury is the most concerning complication due to bony overhangs or an abnormal course of the facial nerve [4][5][6] .…”
Section: Discussionmentioning
confidence: 99%
“…Table 1. St Thomas's classification of round window accessibility with recommended type of surgical approach [5] Figure 1. St. Thomas' Classification of round window accessibility with recommended type of surgical approach [5] Classification of Round Window Accessibility The surgical notes for the 25 patients were retrieved and analysed.…”
Section: Classification Descriptionmentioning
confidence: 99%
“…St Thomas's classification of round window accessibility with recommended type of surgical approach [5] Figure 1. St. Thomas' Classification of round window accessibility with recommended type of surgical approach [5] Classification of Round Window Accessibility The surgical notes for the 25 patients were retrieved and analysed. Amongst the cases where the status of the MPFN was mentioned, there were three where the surgeon specifically stated that he had uncovered the bone overlying the MPFN, and they were also captured on HRCT.…”
Section: Classification Descriptionmentioning
confidence: 99%
See 1 more Smart Citation